" TOOTH ABSCESS " - Do'smuxamedova Shirina Nodirbek Qizi (Western European Studies, 2025)
A tooth abscess is an inflammation of the tissues around a tooth caused by an infection that results in the formation of pus. An abscess usually develops as a result of unnoticed or untreated dental caries, dental trauma, or gum disease
Keywords: Abscess; Odontogenic infection; Maxillofacial surgery; Maxillofacial region